2019
DOI: 10.1111/acem.13494
|View full text |Cite
|
Sign up to set email alerts
|

Access to Federally Qualified Health Centers and Emergency Department Use Among Uninsured and Medicaid‐insured Adults: California, 2005 to 2013

Abstract: Background: While improved access to safety net primary care providers, like federally qualified health centers (FQHCs), is often cited as a route to alleviate potentially preventable emergency department (ED) visits, no studies have longitudinally established the impact of improving access to FQHCs on ED use among Medicaidinsured and uninsured adults. We aimed to determine whether improved access to FQHCs was associated with lower ED use by uninsured and Medicaid-insured adults. Methods:Using data from the Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…While the receipt of primary care in general-and at FQHCs specifically-has been previously associated with a reduction in ED visits, nonemergent ED visits, and potentially avoidable hospitalizations, few of these studies have included dual enrollees, fewer still have been national in scope, and most have used aggregated-rather than person-level-data. [30][31][32][33][34][35][36]56 This limits the ability to examine the relationship between FQHC use and hospital-based care. By contrast,…”
Section: Discussionmentioning
confidence: 99%
“…While the receipt of primary care in general-and at FQHCs specifically-has been previously associated with a reduction in ED visits, nonemergent ED visits, and potentially avoidable hospitalizations, few of these studies have included dual enrollees, fewer still have been national in scope, and most have used aggregated-rather than person-level-data. [30][31][32][33][34][35][36]56 This limits the ability to examine the relationship between FQHC use and hospital-based care. By contrast,…”
Section: Discussionmentioning
confidence: 99%
“…Although we had no information on the quality or level of behavioral health integration of primary care delivered at CHCs, previous work may help contextualize our findings. Nath and colleagues (26) found that an increase in geographic density of CHCs within a county corresponds with reduced ED visits (for any condition) only among the uninsured population. It remains plausible that general primary care visits at CHCs may have identified unmet mental health care needs for the uninsured population and substituted for psychiatric ED care.…”
Section: Discussionmentioning
confidence: 99%
“…The prior literature that examines area-level effects of FQHC availability or expansions have used a range of catchment areas for FQHCs, including county, metropolitan statistical area, and hospital referral region [ 4 , 5 , 10 ]. However, the actual service areas of FQHCs depend on the number, size, and geographic spread of each FQHC’s delivery sites and the local availability of non-FQHC primary care providers; the actual service areas could cross boundaries of predefined catchment areas.…”
Section: Methodsmentioning
confidence: 99%
“…The existing evidence on FQHC use and ED visits is largely based on cross-sectional comparisons and has mixed findings [6][7][8][9]. One countylevel study in California that examined the impact of expanded FQHC capacity found that increased geographic density of FQHCs reduced ED visits for uninsured residents, but not Medicaid enrollees; other measures of local FQHC capacity were not associated with changes in ED visits [10].…”
Section: Introductionmentioning
confidence: 99%